Vascular contribution to cognitive impairment and dementia (VCID): proceedings of 2025 workshop of the Jackson Laboratory - Mehwish Anwer; Tetiana Poliakova; Ricardo D’Oliveira Albanus; Mohammad Iqbal H. Bhuiyan; Adam M. Brickman; Soumilee Chaudhuri; Leah Cuddy; Maxwell Eisenbaum; Kate Foley; Douglas B. Gould; Catherine Hall; Costantino Iadecola; et al. (Mammalian Genome, 2026)
The first Vascular Contributions to Cognitive Impairment and Dementia (VCID) Workshop, held on May12-16, 2025 at The Jackson Laboratory, provided scientific content and career development training in the latest developments in VCID and Alzheimer’s Disease (AD) and related dementia (ADRD). The Workshop aimed to foster interdisciplinary collaborations and empower the next generation of diverse scientists to advance ADRD research from mechanism to intervention. The meeting placed a strong emphasis on neurovascular pathology, its central role in ADRD pathogenesis, its modulation by both central and peripheral factors, and the critical need to dissect the mechanistic basis of VCID through experimental models. The workshop included talks from both faculty and trainees and was bookended by two keynote addresses by Drs. Donna Wilcock and Costantino Iadecola, leaders and pioneers in the VCID field. The second VCID workshop is planned for April 28-May 1, 2026, to be held at Washington University in St. Louis.

Experimental trace element partition coefficients for upper mantle pyroxenites coexisting with H2O with CO2, NaCl and NH3 fluids - Matthew J. M. Phillips; Svyatoslav S. Shcheka; Stephen F. Foley (Contributions to Mineralogy and Petrology, 2026)
Experimental determinations of trace element distribution between rocks/minerals and fluids at mantle pressures and temperatures have concentrated on eclogite and on fluids containing H 2 O with or without the addition of NaCl. Here we present data for websterite (pyroxenite) coexisting with five different fluids: H 2 O, H 2 O+CO 2 , H 2 O+NaCl, H 2 O+CO 2 +NaCl and H 2 O+NH 3 . All experiments were conducted at 1.5 GPa and 800˚C using glassy carbon fluid traps that were kept in a frozen state following experiments until trace elements in the fluid traps were analysed by laser cryoablation-ICP-MS. Results show that Rb, Ba, Sr, Pb and Li are fluid-mobile, with lower rock/fluid partition coefficients (D Rock/Fluid ) for all mixed fluids relative to pure H 2 O. Lowest values (0.0004–0.123) are found for H 2 O+NH 3 fluids. Almost all for the REE are 2 O+CO 2 +NaCl and H 2 O+NH 3 fluids, as are the HFSE, which also show lower D Rock/Fluid than for eclogites, with or without NaCl. Re and Pt are fluid-mobile, with D Re Pt and lowest values for both in H 2 O+CO 2 fluids. The first row transition elements show D-values ranging from 0.0004 to 2.88 with only 4 of 35 data points > 1. D Rock/Fluid increase in the order Cu Rock/Fluid ,particularly low-Al clinpyroxenes.

Radiological characterisation and inter-laboratory comparison of naturally occurring radioactive materials (NORM) in building materials used in Ireland - R.E. Djabou; M. Dodek; C. Sainz; I. Fuente; L. León Vintró; O. Hanley; J. Goggins; M. Foley (Science of The Total Environment, 2026)

Genomic insights into the evolutionary history and cryptic diversity of two-toed sloths (Choloepus) in Amazonia - Larissa S. Arantes; Luísa S. Marins; Linda Hagberg; Radarane Santos Sena; Benoit de Thoisy; Marta Svartman; Mariluce Rezende Messias; Cláudia R. Silva; Nicole M. Foley; William J. Murphy; Camila C. Ribas; Fabrício R. Santos; et al. (Molecular Phylogenetics and Evolution, 2026)

Boater Compliance with Speed Regulations in High-Risk Areas for Marine Turtle Watercraft Strikes - Mariana M. P. B. Fuentes; Jessica Z. D’Auria; Stephanie Viegas Gkionis; Camille Kynoch; Joshua C. Manning; Sophie Mills; Sophie Rosengarten; Julia Saltzman; Armando Barsante Santos; Allen M. Foley (Coastal Management, 2026)

Gamma emissions from NORM in building materials: A position paper on national transposition of the Euratom basic safety standard - M. Dodek; R.E. Djabou; C. Sainz; I. Fuente; L.L. Vintró; O. Hanley; J. Goggins; M. Foley (Journal of Environmental Radioactivity, 2026)

Associations between monthly fine particulate matter and ozone exposure, and postneonatal infant mortality in the United States, 2005–2017 - Sanjida J. Mowla; Alison K. Krajewski; Adrien A. Wilkie; Kristen Foley; Kristen M. Rappazzo; Thomas J. Luben (Science of The Total Environment, 2026)

Matched case-control study of air pollution and infant mortality in North Carolina - Thomas J. Luben; Alison K. Krajewski; Adrien A. Wilkie; Kristen Foley; Kristen M. Rappazzo (Environmental Research, 2026)

The role of bacterial rrn copy number in shaping ecological strategies in soil: Is it time to re-evaluate this functional trait? - Jaron Adkins; Karen M. Foley; Karen H. Beard; Trisha B. Atwood; Bonnie G. Waring (Soil Biology and Biochemistry, 2026)

Early Pliocene (Zanclean) sea surface temperature for PlioMIP3 - Harry J. Dowsett; Kevin M. Foley (Global and Planetary Change, 2026)

Advancing Earth System Science With the NASA Plankton, Aerosol, Cloud, Ocean Ecosystem ( PACE ) Satellite Mission - P. Jeremy Werdell; Brian Cairns; Skyelar A. Caplan; Ivona Cetinić; Sean R. Foley; Bryan A. Franz; Meng Gao; Zachary T. Fasnacht; K. Fred Huemmrich; Amir Ibrahim; Kirk D. Knobelspiesse; Antonio Mannino; et al. (Global Change Biology, 2026)
Earth observation satellites transform our understanding of Earth's biological, atmospheric, and surface systems. The Plankton, Aerosol, Cloud, ocean Ecosystem (PACE) mission, launched in 2024, represents NASA's latest investment in multidisciplinary Earth system science, building upon multi‐decadal heritage while introducing revolutionary capabilities. Since launch, PACE has extended and improved upon NASA's 30+ years of global satellite observations of our living ocean, atmosphere, and land, and initiated an advanced set of climate‐ and applications‐relevant data records. Mission goals include extending and improving upon systematic ocean color, aerosol, cloud, and terrestrial data records for Earth system studies, and addressing emerging science questions related to socioeconomic applications. PACE helps assess ocean health by determining the distribution of aquatic phytoplankton. In doing so, it is the first mission to provide daily, global measurements that will enable prediction of the “boom‐bust” cycle of fisheries, the appearance of harmful algae, and other factors that affect commercial and recreational industries. PACE also observes clouds and tiny airborne particles known as aerosols that influence air quality and absorb and reflect sunlight, thus warming and cooling the atmosphere. Many stakeholders rely on these key data to forecast weather, visibility, and air quality. Also, PACE provides novel and near‐daily views of land surfaces, collectively extending heritage vegetation time series while introducing novel terrestrial measurements previously only achievable at local scales. PACE ultimately provides observations that benefit Earth system research and society as a whole in ways that other current satellites cannot. As it passes its two‐year anniversary, the mission exemplifies how combining hyperspectral radiometry with multi‐angle polarimetry enables transformative Earth system science, addressing critical uncertainties while establishing new paradigms for integrated observations of our changing planet. This review examines how PACE fills critical gaps across aquatic, terrestrial, and atmospheric science disciplines.

Drought Reduces Formation, but Enhances Persistence, of Mineral‐Associated Organic Matter in a Grassland Soil - Noah W. Sokol; Megan M. Foley; Steven J. Blazewicz; Nicole DiDonato; Katerina Estera‐Molina; Mary Firestone; Alex Greenlon; Bruce A. Hungate; William Kew; Ljiljana Paša‐Tolić; Eric Slessarev; Jennifer Pett‐Ridge (Global Change Biology, 2026)
Drought effects are pervasive in terrestrial ecosystems, yet there is limited understanding of how drought impacts the transformation of plant carbon (C) inputs to mineral‐associated organic matter (MAOM)—the largest and slowest‐cycling pool of soil organic carbon (SOC). In a 12‐week 13 C‐CO 2 greenhouse labeling experiment, we tracked the formation of MAOM derived from the two dominant sources of plant C input to the mineral soil—living root inputs ( 13 C‐rhizodeposits) and decaying root inputs ( 13 C‐root detritus)—under normal moisture and droughted conditions in a semiarid grassland soil. At the end of the 12‐week period, we also measured the persistence of 13 C‐MAOM formed from rhizodeposits versus root detritus via a subsequent persistence assay. Drought reduced the formation of MAOM derived from living roots by decreasing rhizodeposits, reducing microbial growth rates, and altering the composition of organic matter, lipids, and metabolites. Drought initially delayed the formation of MAOM derived from root detritus by slowing the early stages of root litter decomposition (week 4–8), but did not decrease total MAOM formation by the end of the 12‐week period. Notably, drought enhanced the persistence of MAOM derived from root detritus, but did not influence the persistence of MAOM derived from rhizodeposits. Our results provide some of the first direct evidence that drought can reduce the formation of MAOM in a grassland soil, but may enhance its persistence, based on the source of plant input from which MAOM is derived.

Impurity poisoning as a mechanism for the formation of zircon oscillatory growth zones - Marisa D. Acosta; James M. Watkins; Denis Fougerouse; Michelle L. Foley; Oliver Plümper; David W. Saxey; Steven M. Reddy; Mark H. Reed (Contributions to Mineralogy and Petrology, 2026)

Pier pressure: 23 years of incidental sea turtle captures at recreational fishing piers along Florida’s Gulf coastline - Robby J. Brannum; Karrie Minch; Morgan Wideroff; Meghan E. Koperski; Colin P. Shea; Allen M. Foley; Robbin N. Trindell (Frontiers in Marine Science, 2025)
Incidental captures of sea turtles during fishing activities affect their populations worldwide. Previous research has documented the impacts of commercial fisheries in nearshore and offshore waters, and research-based minimization measures are now required to reduce sea turtle take. However, incidental captures of juvenile-to-adult sea turtles also occur in recreational fisheries in nearshore and inshore waters, although the magnitude and distribution of these events are poorly understood. We analyzed Florida Sea Turtle Stranding and Salvage Network (STSSN) reports between 2000 and 2022 to identify sea turtles incidentally captured by recreational anglers from fishing piers along Florida’s Gulf coastline. We used a negative binomial regression model to quantify temporal and spatial changes in the mean number of pier-captured sea turtles reported at Gulf piers over the 23-year study period. There were 452 documented incidents of loggerheads ( Caretta caretta ), green turtles ( Chelonia mydas ), and Kemp’s ridleys ( Lepidochelys kempii ) hooked at 33 different piers. Juvenile and subadult turtles of all three species were pier-captured as well as adult loggerhead and Kemp’s ridley turtles. The number of turtles for each of the three species captured varied over time, but overall the number of reported captures increased regionally over the 23-year study. Most turtles captured and recovered at recreational fishing piers were successfully rehabilitated and released back to the wild (84.7.%). The observed increases in sea turtle pier capture reports likely reflect some combination of increased turtle numbers in the nearshore environment, increased use of piers as foraging habitat, and increased reporting requirements and effort. This analysis offers insights into the complex interactions between sea turtles and pier-based recreational fishing in the Gulf and could help inform conservation efforts while supporting responsible recreational fishing practices.

Navigating danger: Watercraft-related mortality of sea turtles in the United States Atlantic and Gulf coastal waters - Mariana M.P.B. Fuentes; Brian A. Stacy; Susan G. Barco; Robert A. DiGiovanni; Karen M. Dourdeville; Kimberly F. Durham; Mark Faherty; Sarah A. Finn; Allen M. Foley; Matthew H. Godfrey; Robert F. Hardy; Lyndsey N. Howell; et al. (Biological Conservation, 2025)

Examining Explicit Stereotype Perceptions of Colorectal Cancer Screening and Diagnosis in the Hispanic Community - Aidan Foley; Bianca Luna-Lupercio; Jessica M. Capaldi; Galen Wiens-Cook; Vinicius Calsavara; Zulfikarali Surani; Sarah-Jeanne Salvy; Jane C. Figueiredo; Robert Haile; Nenette A. Cáceres; Celina H. Shirazipour (Journal of Cancer Education, 2025)
Cancer is a leading cause of death among Hispanic people in the USA. One potential reason is low adherence to cancer screening guidelines, particularly for colorectal cancer (CRC). Previous research suggests that low CRC screening may be linked to negative stereotypes associated with cancer and CRC screening methods. The purpose of this study was to examine explicit stereotype perceptions of CRC screening and diagnosis in the Hispanic community. Hispanic adults ( n = 279) were asked to read three vignettes presenting a gender-neutral individual who was either diagnosed with CRC, completed colonoscopies for CRC screening, or was a control (no cancer information provided). Using the Stereotype Content Model approach, after reading each vignette, participants completed measures assessing explicit perceptions (warmth and competence) of the individual. Linear mixed-effects models were fitted to evaluate differences in perceptions between vignettes. The main effect indicated no significant difference in warmth or competence perceptions based on vignette condition ( p = .78). However, there was a significant difference in explicit perceptions based on the study participant’s Hispanic heritage, gender, and age ( p s < .05). Findings emphasize differences in explicit perceptions of cancer and cancer screening based on important demographic characteristics. Thus, important implications include the need for cancer educational materials and interventions to consider the important heterogeneity within the Hispanic community. Future CRC screening interventions should be tailored based on Hispanic heritage, gender, and age.

Composition, Growth, Succession, and Function in the Cladophora Microbiome: Insights From Quantitative Stable Isotope Probing and NanoSIMS Imaging - Raina M. Fitzpatrick; Bruce A. Hungate; Mary Power; Megan Foley; Ty Samo; Egbert Schwartz; Micheala Hayer; Peter K. Weber; Jennifer Pett‐Ridge; Jane C. Marks (Environmental Microbiology, 2025)
The branching green macroalga Cladophora glomerata and its epiphytic microbiome dominate summer biomass in the Eel River, a Northern California river under Mediterranean (summer drought, winter rain) seasonality. Green Cladophora streamers proliferate in early summer, then change to yellow and then red‐brown as epiphyte loads increase. We characterised successional changes in epiphytic bacteria on Cladophora , examining both community composition and growth rates, using quantitative Stable Isotope Probing (qSIP) and 16S rRNA gene amplicon sequencing. The number of bacterial taxa increased with succession while growth rates peaked in the middle stage. NanoSIMS imaging confirmed high sulphur (S) concentrations in Cladophora cell walls relative to surrounding biomass, coinciding with a bloom of sulphur bacteria (bacteria that reduce or oxidise sulphur/sulphates). In general, relative abundances and growth rates were independent, indicating that either metric alone is insufficient for understanding how taxonomy and functional groups affect ecosystem processes. For instance, the relative abundance of nitrogen fixers peaked in the late summer when their relative growth rates were slowest. Such patterns may be driven by space competition limiting growth. Together, changes in abundance and relative growth rates suggest different limiting factors for different functional groups in the Cladophora microbiome at multiple successional stages.

Recombination-aware phylogenomics - Frank T. Burbrink; Dylan DeBaun; Nicole M. Foley; William J. Murphy (Trends in Ecology & Evolution, 2025)

Regional differentiation in somatic growth and maturation attributes for loggerhead sea turtles (Caretta caretta) in the Northwest Atlantic - Larisa Avens; Margaret M. Lamont; Allen M. Foley; Benjamin M. Higgins; Lyndsey N. Howell; Gretchen Lovewell; Donna J. Shaver; Brian A. Stacy; J. Shelby Walker; Jamie M. Clark; Amy A. Wallace; Hannah B. Vander Zanden (Marine Biology, 2025)

Counterclockwise P-T-t path, cyclic crustal anatexis and magmatic tempo in accretionary orogens: A case study in the Devonian arc of Central Patagonia, Argentina - Emiliano M. Renda; Paulo Marcos; Sebastian Oriolo; Benita Putlitz; Lukas Baumgartner; Pablo González; Michelle L. Foley; Victor Ruiz González; Haroldo Vizán (Gondwana Research, 2025)

Overwintering humpback whales adapt foraging strategies to shallow water environments at the mouth of the Chesapeake Bay, Virginia, USA - Jeanne M. Shearer; Heather J. Foley; Zachary T. Swaim; Vincent M. Janik; Andrew J. Read (Marine Mammal Science, 2025)
Some humpback whales from the Northwestern Atlantic population forgo migration to the Caribbean, spending winter months feeding along the U.S. mid‐Atlantic coast. We studied the foraging behavior of these whales at the mouth of the Chesapeake Bay, Virginia during winter from 2017 to 2022. While shipping channels here reach depths of up to 30 m, most of the area is 11–15 m deep. This shallow‐water environment poses physical constraints on classical humpback whale feeding modes. We deployed 20 digital acoustic tags (DTAGs) on humpback whales and identified foraging lunges from accelerometer data, detecting 788 lunges from 10 animals. Tagged whales averaged a single lunge per dive, lunging primarily in a horizontal orientation, with limited maneuvering compared to other study sites. Our results indicate that some elements of humpback whale foraging behavior are conserved across environments, but that the shallow depths in our study area constrain how animals are able to feed. The relatively high lunge rates we observed suggest this area is an important foraging ground. However, foraging in shipping channels increases the risk of ship strikes, which frequently occur in this area.

Killer whales in the Gulf of Mexico and North Atlantic off the Southeastern United States - Kevin P. Barry; Keith D. Mullin; Katherine Maze-Foley; Lynsey A. Wilcox Talbot; Patricia E. Rosel; Melissa S. Soldevilla; Laura Aichinger Dias; M. Rafael Ramírez-León; Jenny A. Litz (Frontiers in Marine Science, 2024)
Killer whales occur in the Gulf of Mexico (GoMex) and the North Atlantic, including off the southeastern United States (SEUS). Data from cetacean surveys during 1990 – 2021 and other sources were combined to assess killer whale biology, including spatial and temporal distribution, social structure, genetics, morphology, acoustics, and predatory behavior. GoMex records occurred predominantly in oceanic waters (>200 m) during spring and summer. SEUS records occurred primarily in winter and spring off the North Carolina region along the shelf-edge and deeper waters, and off the east coast of Florida. Photo-identification analysis of GoMex killer whales resulted in 49 individuals sighted up to seven times with sighting histories up to 26 years, and social analysis provided evidence of long-term relationships up to 16 years. The GoMex genetic samples revealed two mtDNA haplotypes, one of which does not match any outside the GoMex. Most GoMex whales had wide non-faint saddle patches and many had cookiecutter shark scars while no scars were noted on SEUS whales. Three groups recorded in the GoMex made few calls, but a group harassing sperm whales produced many. Cetaceans and tuna are known prey in the GoMex and SEUS, respectively. Directed studies of killer whales in the GoMex areas would be difficult to implement as this species is very rare. It is therefore important to pursue ongoing efforts to collect behavioral, acoustic and any biological samples that will contribute to improve our understanding of the biology and ecology of killer whales in tropical and subtropical regions.

Reevaluating safety pharmacology respiratory studies within the ICH S7A core battery: A multi-company evaluation of preclinical utility and clinical translation - G.S. Friedrichs; M.M. Abernathy; D. Ackley; M. Clark; J.K. DaSilva; C.M. Foley; A. Greiter-Wilke; K.A Henderson; J.J. Kremer; B.H. Morimoto; S. Paglialunga; M.K. Pugsley; et al. (Regulatory Toxicology and Pharmacology, 2024)

Organophosphate ester flame retardant chemicals and maternal depression during pregnancy - Ixel Hernandez-Castro; Sandrah P. Eckel; Caitlin G. Howe; Max T. Aung; Kurunthachalam Kannan; Morgan Robinson; Helen B. Foley; Tingyu Yang; Mario J. Vigil; Xinci Chen; Brendan Grubbs; Laila Al-Marayati; et al. (Environmental Research, 2024)

Linking Vegetation Characteristics of Madagascar’s Spiny Forest to Habitat Occupancy of Lepilemur petteri - Yedidya R. Ratovonamana; Celina Apel; Davidson H. Hajanantenaina; William J. Foley; Daniel Kübler; Stella Nevermann; S. Jacques Rakotondranary; Eleanor M. Stalenberg; Jörg U. Ganzhorn (International Journal of Primatology, 2024)
Climatic changes with unpredictable weather conditions have negative effects on many primates. With several lemur species reaching their ecological limits in the dry and hypervariable spiny forest, Madagascar might provide an example for understanding adaptations of primates to unpredictable conditions. Here, we aimed to identify vegetation characteristics that allow Lepilemur petteri to persist in an environment at the limit of its ecological niche. For this, we linked the patchy distribution of the species to vegetation characteristics described on the ground and by remote sensing reflecting primary production (Enhanced Vegetation Index from MODIS) for 17 sites in nine regions, spread over 100 km along Tsimanampetsotse NP. We verified the results on a smaller scale by radio-tracking and vegetation analyses related to home ranges of 13 L. petteri . Remote sensing indicated that L. petteri is more likely to occur in forests where the variation of the annual primary production and the interannual variability of the month with the lowest primary production are low. Lepilemur petteri was more likely to occur with increasing densities of large trees, large food tree species (diameter ≥ 10 cm) and octopus trees ( Alluaudia procera ). Alluaudia procera provide food year-round and shelter in the spiny forest where large trees with holes are absent. High tree species diversity might buffer food availability against failure of certain tree species to produce food. These findings illustrate limiting constraints of climatic hypervariability for lemurs and indicate benefits of forest restoration with high numbers of tree species for biodiversity conservation.

Testing food web theory in a large lake: The role of body size in habitat coupling in Lake Michigan - Bryan M. Maitland; Harvey A. Bootsma; Charles R. Bronte; David B. Bunnell; Zachary S. Feiner; Kari H. Fenske; William W. Fetzer; Carolyn J. Foley; Brandon S. Gerig; Austin Happel; Tomas O. Höök; Friedrich W. Keppeler; et al. (Ecology, 2024)
The landscape theory of food web architecture (LTFWA) describes relationships among body size, trophic position, mobility, and energy channels that serve to couple heterogenous habitats, which in turn promotes long‐term system stability. However, empirical tests of the LTFWA are rare and support differs among terrestrial, freshwater, and marine systems. Further, it is unclear whether the theory applies in highly altered ecosystems dominated by introduced species such as the Laurentian Great Lakes. Here, we provide an empirical test of the LTFWA by relating body size, trophic position, and the coupling of different energy channels using stable isotope data from species throughout the Lake Michigan food web. We found that body size was positively related to trophic position, but for a given trophic position, organisms predominately supported by pelagic energy had smaller body sizes than organisms predominately supported by nearshore benthic energy. We also found a hump‐shaped trophic relationship in the food web where there is a gradual increase in the coupling of pelagic and nearshore energy channels with larger body sizes as well as higher trophic positions. This highlights the important role of body size and connectivity among habitats in structuring food webs. However, important deviations from expectations are suggestive of how species introductions and other anthropogenic impacts can affect food web structure in large lakes. First, native top predators appear to be flexible couplers that may provide food web resilience, whereas introduced top predators may confer less stability when they specialize on a single energy pathway. Second, some smaller bodied prey fish and invertebrates, in addition to mobile predators, coupled energy from pelagic and nearshore energy channels, which suggests that some prey species may also be important integrators of energy pathways in the system. We conclude that patterns predicted by the LTFWA are present in the face of species introductions and other anthropogenic stressors to a degree, but time‐series evaluations are needed to fully understand the mechanisms that promote stability.

Long-term ambient sulfur dioxide exposure during gestation and preterm birth in North Carolina, 2003–2015 - Adrien A. Wilkie; Thomas J. Luben; Kristen M. Rappazzo; Kristen M. Foley; Courtney G. Woods; Marc L. Serre; David B. Richardson; Julie L. Daniels (Atmospheric Environment, 2024)

Integrated textural and geochemical analysis of igneous zircon by atom probe tomography - Michelle L. Foley; Elias M. Bloch; Stephan S.A. Gerstl; Benita Putlitz; Lukas P. Baumgartner (Contributions to Mineralogy and Petrology, 2024)
Mechanisms relating to growth and/or compositional modification of zircon occur at the atomic scale. For felsic igneous systems, processes responsible for growth patterns in zircon have previously remained elusive as the volume of material needed to analyze these compositional features using traditional in-situ methods is considerably larger than the typical sub-micron scale distribution of trace elements. To illuminate some of these driving forces, we characterize and quantify minor and trace element concentrations in igneous zircon grains by combining methods of cathodoluminescence (CL) imaging, electron microprobe microanalysis (EMPA) elemental maps for Hf, Y, Yb and U or Th, and atom probe tomography (APT). We focus on igneous zircon from the Chon Aike Silicic Large Igneous Province (Patagonia) that provide novel insights into (1) dissolution and re-crystallization during crustal anatexis, (2) crystallization to produce oscillatory zonation patterns that are typical of igneous zircons, and (3) the incorporation of trace element impurities (e.g., P, Be, and Al) at the nanoscale. Significantly, these APT volumes provide nanoscale sampling of boundaries between oscillatory growth zones in an igneous zircon to reveal compositional zoning of Y and, to a lesser extent P, which appear as high-angle, planar features. These concentration boundaries measured on the order of 10 to 12 nm are difficult to reconcile with proposed mechanisms for generating fine-scaled oscillations. Lastly, we fit diffusional profiles to measured Y concentrations to provide an estimate on the maximum timescales of zircon growth prior to eruption, as a function of the temperature at which diffusion occurred. When combined with known pressure-temperature-time paths for the magmatic system considered, these extremely short diffusion profiles that are resolvable by APT provide a powerful method to constrain timescales of crystal growth.

Novel Rickettsia and host records for argasid ticks, including Alveonasus cooleyi, on wild mammals in Baja California, Mexico - Andrés M. López-Pérez; Laura Backus; Lorenza Beati; Hans Klompen; Francesca Rubino; Janet Foley (Experimental and Applied Acarology, 2024)

Prenatal air pollution exposure is associated with inflammatory, cardiovascular, and metabolic biomarkers in mothers and newborns - Nan Ji; Sandrah P. Eckel; Helen Foley; Tingyu Yang; Fred Lurmann; Brendan H. Grubbs; Rima Habre; Theresa M. Bastain; Shohreh F. Farzan; Carrie V. Breton (Environmental Research, 2024)

Song fragments recorded on a tagged juvenile humpback whale ( Megaptera novaeangliae ) on a winter feeding ground at the mouth of the Chesapeake Bay, Virginia, USA - Dana L. Adcock; Jeanne M. Shearer; Heather J. Foley; Zach T. Swaim; Andrew J. Read (Marine Mammal Science, 2024)

The path from root input to mineral-associated soil carbon is dictated by habitat-specific microbial traits and soil moisture - Noah W. Sokol; Megan M. Foley; Steven J. Blazewicz; Amrita Bhattacharyya; Nicole DiDonato; Katerina Estera-Molina; Mary Firestone; Alex Greenlon; Bruce A. Hungate; Jeffrey Kimbrel; Jose Liquet; Marissa Lafler; et al. (Soil Biology and Biochemistry, 2024)

Fluid loss to the fore-arc controls the recycling efficiency of nitrogen in subduction zones - Michael W. Förster; Chunfei Chen; Stephen F. Foley; Olivier Alard; Gregory M. Yaxley (Chemical Geology, 2024)

Indole-3-acetic acid promotes growth in bloom-forming Microcystis via an antioxidant response - Hunter R. Baylous; Matthew F. Gladfelter; Malia I. Gardner; Madalynn Foley; Alan E. Wilson; Morgan M. Steffen (Harmful Algae, 2024)

Prenatal exposures to organophosphate ester metabolites and early motor development in the MADRES cohort - Ixel Hernandez-Castro; Sandrah P. Eckel; Xinci Chen; Tingyu Yang; Mario J. Vigil; Helen B. Foley; Kurunthachalam Kannan; Morgan Robinson; Brendan Grubbs; Deborah Lerner; Nathana Lurvey; Laila Al-Marayati; et al. (Environmental Pollution, 2024)

Identifying crustal contributions in the Patagonian Chon Aike Silicic Large Igneous Province - Michelle L. Foley; Benita Putlitz; Lukas P. Baumgartner; Emiliano M. Renda; Alexey Ulianov; Guillaume Siron; Massimo Chiaradia (Contributions to Mineralogy and Petrology, 2023)
The volcanic rocks of the Chon Aike Silicic Large Igneous Province (CASP) are recognized as magmas dominantly produced by crustal anatexis. Investigating the zircon of the CASP provides an opportunity to gain further insight into geochemical and isotopic differences of the potential magmatic sources (i.e., crust versus mantle), to identify crustal reservoirs that contributed to the felsic magmas during anatexis, and to quantify the contributions of the respective sources. We present a combined zircon oxygen and hafnium isotope and trace element dataset for 16 volcanic units of the two youngest volcanic phases in Patagonia, dated here with LA-ICP-MS U–Pb geochronology at ca. 148–153 Ma (El Quemado Complex, EQC) and ca. 159 Ma (western Chon Aike Formation, WCA). The EQC zircon have 18 O-enriched values (δ 18 O from 7 to 9.5‰) with correspondingly negative initial εHf values (− 2.0 to − 8.0). The WCA zircon have δ 18 O values between 6 and 7‰ and εHf values ranging between − 4.0 and + 1.5. Binary δ 18 O-εHf mixing models require an average of 70 and 60% melt derived from partial melting of isotopically distinct metasedimentary basements for the EQC and WCA, respectively. Zircon trace element compositions are consistent with anatexis of sedimentary protoliths derived from LIL-depleted upper continental crustal sources. The overlap between a high heat flux environment (i.e., widespread extension and lithospheric thinning) during supercontinental breakup and a fertile metasedimentary crust was key in producing voluminous felsic volcanism via anatexis following the injection and emplacement of basaltic magmas into the lower crust.

Interspecific interactions, human proximity, and season affect spatiotemporal structure of a Mojave Desert wetlands rodent community with a highly endangered species - Andrés M. López-Pérez; Peter Haswell; Deana L. Clifford; Janet Foley (Mammalian Biology, 2023)
We analyzed the influences of interspecific interactions and environmental factors on rodent community assembly in Mojave Desert wetlands that support the endangered Amargosa vole ( Microtus californicus scirpensis ). A total of 4927 rodents in six species were captured from 2010 to 2021 within 15 marshes, most frequently including Amargosa voles, harvest mice ( Reithrodontomys megalotis ), and house mice ( Mus musculus ), an invasive species. The structure of the community varied considerably over time and by marsh, driven mainly by reductions in harvest mice and increases in Amargosa voles and house mice between 2014 and 2017, and then reductions in Amargosa voles between 2018 and 2021. Northern marshes were dominated by voles, and southern marshes by house mice. Primary determinants of rodent capture rates were interspecific interactions, human proximity, and season. There was a significant inverse relationship between vole and house mouse captures per session, suggesting competitive exclusion. Distance to the nearest town was positively associated with the numbers of voles and negatively associated with the numbers of harvest mice, suggesting that voles may be more sensitive to human disturbance than other rodents. Amargosa voles and harvest mice had annual population cycles with peaks between July and September occurring 6–7 months after rainfall. Our results allow for valuable insight into the influences on community dynamics in desert rodents and highlight that conservation efforts that support Amargosa voles may simultaneously help control house mouse abundance and expansion.

Reducing the time-dependent climate impact of intensive agriculture with strategically positioned short rotation coppice willow - David Livingstone; Beatrice M. Smyth; Rachel Cassidy; Simon T. Murray; Gary A. Lyons; Aoife M. Foley; Christopher R. Johnston (Journal of Cleaner Production, 2023)

First report of Colletotrichum fioriniae infections in brown marmorated stink bugs, Halyomorpha halys - Jennifer B. González; Chloe A. Lambert; Alexandra M. Foley; Ann E. Hajek (Journal of Invertebrate Pathology, 2023)

Sex-specific effects of prenatal organophosphate ester (OPE) metabolite mixtures and adverse infant birth outcomes in the maternal and developmental risks from environmental and social stressors (MADRES) pregnancy cohort - Ixel Hernandez-Castro; Sandrah P. Eckel; Caitlin G. Howe; Zhongzheng Niu; Kurunthachalam Kannan; Morgan Robinson; Helen B. Foley; Brendan Grubbs; Laila Al-Marayati; Deborah Lerner; Nathana Lurvey; Max T. Aung; et al. (Environmental Research, 2023)

Geographic and taxonomic variation in adaptive capacity among mountain-dwelling small mammals: Implications for conservation status and actions - Erik A. Beever; Jennifer L. Wilkening; Peter D. Billman; Lindsey L. Thurman; Kristina A. Ernest; David H. Wright; Alisha M. Gill; April C. Craighead; Nolan A. Helmstetter; Leona K. Svancara; Meghan J. Camp; Sabuj Bhattacharyya; et al. (Biological Conservation, 2023)

Production pathways for profitability and valuing ecosystem services for willow coppice in intensive agricultural applications - David Livingstone; Beatrice M. Smyth; Erin Sherry; Simon T. Murray; Aoife M. Foley; Gary A. Lyons; Christopher R. Johnston (Sustainable Production and Consumption, 2023)

Recovering an endangered vole and its habitat may help control invasive house mice - Peter M. Haswell; Andrés M. López-Pérez; Deana L. Clifford; Janet E. Foley (Food Webs, 2023)

Transition from tholeiitic to alkali basalts via interaction between decarbonated eclogite-derived melts and peridotite - Qiuhong Xie; Zhaochong Zhang; Stephen F. Foley; Chunfei Chen; Zhiguo Cheng; Yu Wang; Weiliang Kong; Yiwen Lv; M. Santosh; Qizhen Jin; Lukáš Krmíček; Xiangkun Zhu (Chemical Geology, 2023)

Dating blueschist-facies metamorphism within the Naga ophiolite, Northeast India, using sheared carbonate veins - Bidyananda Maibam; Richard M. Palin; Axel Gerdes; Richard W. White; Stephen Foley (International Geology Review, 2023)

Active populations and growth of soil microorganisms are framed by mean annual precipitation in three California annual grasslands - Megan M. Foley; Steven J. Blazewicz; Karis J. McFarlane; Alex Greenlon; Michaela Hayer; Jeffrey A. Kimbrel; Benjamin J. Koch; Victoria L. Monsaint-Queeney; Keith Morrison; Ember Morrissey; Bruce A. Hungate; Jennifer Pett-Ridge (Soil Biology and Biochemistry, 2023)

Changing how you look at climate change: attention bias modification increases attention to climate change - Joshua M. Carlson; Madeline Voltz; John Foley; Lisa Gentry; Lin Fang (Climatic Change, 2022)

Taking flight: An ecological, evolutionary and genomic perspective on bat telomeres - Megan L. Power; Nicole M. Foley; Gareth Jones; Emma C. Teeling (Molecular Ecology, 2022)
Over 20% of all living mammals are bats (order Chiroptera). Bats possess extraordinary adaptations including powered flight, laryngeal echolocation and a unique immune system that enables them to tolerate a diversity of viral infections without presenting clinical disease symptoms. They occupy multiple trophic niches and environments globally. Significant physiological and ecological diversity occurs across the order. Bats also exhibit extreme longevity given their body size with many species showing few signs of ageing. The molecular basis of this extended longevity has recently attracted attention. Telomere maintenance potentially underpins bats’ extended healthspan, although functional studies are still required to validate the causative mechanisms. In this review, we detail the current knowledge on bat telomeres, telomerase expression, and how these relate to ecology, longevity and life‐history strategies. Patterns of telomere shortening and telomerase expression vary across species, and comparative genomic analyses suggest that alternative telomere maintenance mechanisms evolved in the longest‐lived bats. We discuss the unique challenges faced when working with populations of wild bats and highlight ways to advance the field including expanding long‐term monitoring across species that display contrasting life‐histories and occupy different environmental niches. We further review how new high quality, chromosome‐level genome assemblies can enable us to uncover the molecular mechanisms governing telomere dynamics and how phylogenomic analyses can reveal the adaptive significance of telomere maintenance and variation in bats.

Characterizing Exposure to Head Acceleration Events in Youth Football Using an Instrumented Mouthpiece - Madison E. Marks; Ty D. Holcomb; N. Stewart Pritchard; Logan E. Miller; Mark A. Espeland; Christopher M. Miles; Justin B. Moore; Kristie L. Foley; Joel D. Stitzel; Jillian E. Urban (Annals of Biomedical Engineering, 2022)

Middle Jurassic–Lower Cretaceous stratigraphy of the northern Great Australian Superbasin: insights from maximum depositional age constraints from the U–Pb detrital zircon record - E. K. Foley; E. M. Roberts; R. A. Henderson; C. N. Todd; E. M. Knutsen; C. Spandler (Australian Journal of Earth Sciences, 2022)

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Dynamic Response of the Thoracolumbar and Sacral Spine to Simulated Underbody Blast Loading in Whole Body Post Mortem Human Subject Tests - Donald Sherman; Karthik Somasundaram; Paul Begeman; Sierra Foley; Jason Greb; Cynthia Bir; Constantine K. Demetropoulos; John M. Cavanaugh (Annals of Biomedical Engineering, 2021)

Adult male Cuvier's beaked whales ( Ziphius cavirostris ) engage in prolonged bouts of synchronous diving - William R. Cioffi; Nicola J. Quick; Heather J. Foley; Danielle M. Waples; Zachary T. Swaim; Jeanne M. Shearer; Daniel L. Webster; Ari S. Friedlaender; Brandon L. Southall; Robin W. Baird; Douglas P. Nowacek; Andrew J. Read (Marine Mammal Science, 2021)
Studies of the social behavior of Cuvier's beaked whales ( Ziphius cavirostris ) are challenging because of their deep‐water habitat usually far from shore and the limited time they spend at the surface. The sociality of these deepest diving mammals is of interest, however, especially for our understanding of how social systems evolve in extreme habitats. High levels of scarring suggest that males compete agonistically for access to females and so we predicted that associations among adult males would be unstable due to competitive exclusion. We tested this prediction by evaluating the diving behavior of animals within social groups off Cape Hatteras, North Carolina, considering diving synchrony a proxy for group membership. Using data from satellite‐linked depth‐recording tags, we found that adult male–male pairs showed extended periods of synchrony in diving behavior, while all pairs that included an adult male with an individual of another age and/or sex dove synchronously for less than a day. We assessed three hypotheses to explain these surprising results: sexual segregation; extended bouts of male–male competition; and the presence of male alliances. Finally, we considered testable predictions to distinguish among these explanations.

Genetic basis of susceptibility to low‐dose paraquat and variation between the sexes in Drosophila melanogaster - Pamela C. Lovejoy; Kate E. Foley; Melissa M. Conti; Samantha M. Meadows; Christopher Bishop; Anthony C. Fiumera (Molecular Ecology, 2021)
Toxicant resistance is a complex trait, affected both by genetics and the environment. Like most complex traits, it can exhibit sexual dimorphism, yet sex is often overlooked as a factor in studies of toxicant resistance. Paraquat, one such toxicant, is a commonly used herbicide and is known to produce mitochondrial oxidative stress, decrease dopaminergic neurons and dopamine (DA) levels, and decrease motor ability. While the main effects of paraquat are well‐characterized, less is known about the naturally occurring variation in paraquat susceptibility. The purpose of this study was to map the genes contributing to low‐dose paraquat susceptibility in Drosophila melanogaster , and to determine if susceptibility differs between the sexes. One hundred of the Drosophila Genetic Reference Panel (DGRP) lines were scored for susceptibility via climbing ability and used in a genome‐wide association study (GWAS). Variation in seventeen genes in females and thirty‐five genes in males associated with paraquat susceptibility. Only two candidate genes overlapped between the sexes despite a significant positive correlation between male and female susceptibilities. Many associated polymorphisms had significant interactions with sex, with most having conditionally neutral effects. Conditional neutrality between the sexes probably stems from sex‐biased expression which may result from partial resolution of sexual conflict. Candidate genes were verified with RNAi knockdowns, gene expression analyses, and DA quantification. Several of these genes are novel associations with paraquat susceptibility. This research highlights the importance of assessing both sexes when studying toxicant susceptibility.

Deconstructing Protein in the Diet and Biomass of Colobine Primates - Katarina D. Evans; William J. Foley; Colin A. Chapman; Jessica M. Rothman (International Journal of Primatology, 2021)

Drivers of longitudinal telomere dynamics in a long‐lived bat species, Myotis myotis - Nicole M. Foley; Eric J. Petit; Thomas Brazier; John A. Finarelli; Graham M. Hughes; Frédéric Touzalin; Sébastien J. Puechmaille; Emma C. Teeling (Molecular Ecology, 2020)
Age‐related telomere shortening is considered a hallmark of the ageing process. However, a recent cross‐sectional ageing study of relative telomere length (rTL) in bats failed to detect a relationship between rTL and age in the long‐lived genus Myotis ( M. myotis and M. bechsteinii ), suggesting some other factors are responsible for driving telomere dynamics in these species. Here, we test if longitudinal rTL data show signatures of age‐associated telomere attrition in M. myotis and differentiate which intrinsic or extrinsic factors are likely to drive telomere length dynamics. Using quantitative polymerase chain reaction, rTL was measured in 504 samples from a marked population, from Brittany, France, captured between 2013 and 2016. These represent 174 individuals with an age range of 0 to 7+ years. We find no significant relationship between rTL and age ( p = .762), but demonstrate that within‐individual rTL is highly variable from year to year. To investigate the heritability of rTL, a population pedigree ( n = 1744) was constructed from genotype data generated from a 16‐microsatellite multiplex, designed from an initial, low‐coverage, Illumina genome for M. myotis . Heritability was estimated in a Bayesian, mixed model framework, and showed that little of the observed variance in rTL is heritable ( h 2 = 0.01–0.06). Rather, correlations of first differences, correlating yearly changes in telomere length and weather variables, demonstrate that, during the spring transition, average temperature, minimum temperature, rainfall and windspeed correlate with changes in longitudinal telomere dynamics. As such, rTL may represent a useful biomarker to quantify the physiological impact of various environmental stressors in bats.

Correcting for within-season demographic turnover to estimate the island-wide population of King Penguins (Aptenodytes patagonicus) on South Georgia - C. M. Foley; W. F. Fagan; H. J. Lynch (Polar Biology, 2020)

Trans-Tasman Cumulative Effects Management: A Comparative Study - Kathryn K. Davies; Karen T. Fisher; Gemma Couzens; Andrew Allison; Elizabeth Ingrid van Putten; Jeffrey M. Dambacher; Melissa Foley; Carolyn J. Lundquist (Frontiers in Marine Science, 2020)

A method to estimate pre‐exploitation population size - Catherine M. Foley; Heather J. Lynch (Conservation Biology, 2020)
Antarctic fur seals ( Arctocephalus gazella ) were commercially exploited on the subantarctic island of South Georgia for over 100 years and nearly driven to extinction. Since the cessation of harvesting, however, their populations have rebounded, and they are now often considered a nuisance species whose impact on the terrestrial landscape should be mitigated. Any evaluation of their current population requires the context provided by their historic, pre‐exploitation abundance, lest ecologists fall prey to shifting baseline syndrome in which their perspective on current abundance is compared only with an altered state resulting from past anthropogenic disturbance. Estimating pre‐exploitation abundance is critical to defining species recovery and setting recovery targets, both of which are needed for the International Union for the Conservation of Nature's recent efforts to develop a green list of recovering species. To address this issue, we reconstructed the South Georgia fur seal harvest from 1786 to 1908 from ship logbooks and other historical records and interpolated missing harvest data as necessary with a generalized linear model fit to the historical record. Using an approximate Bayesian computation framework, harvest data, and a stochastic age‐structured population model, we estimated the pre‐exploitation abundance of Antarctic fur seals on South Georgia was 2.5 million females (95% CI 1.5–3.5 million). This estimate is similar to recent abundance estimates, and suggests current populations, and the ecological consequences of so many fur seals on the island, may be similar to conditions prior to human harvest. Although the historic archive on the fur sealing era is unavoidably patchy, the use of archival records is essential for reconstructing the past and, correspondingly, to understanding the present. Article impact statement : Defining species recovery requires an understanding of baseline population state, which can be estimated through statistical methods.

A Qualitative Systematic Review of Cigarette Smoking Cessation Interventions for Persons Living with HIV - Lilli Mann-Jackson; David Choi; Erin L. Sutfin; Eunyoung Y. Song; Kristie L. Foley; Aimee M. Wilkin; Caryn G. Morse; Nicole F. Rojas; Timothy S. Oh; Scott D. Rhodes (Journal of Cancer Education, 2019)

Open science and meta‐analysis allow for rapid advances in ecology: A response to Menegotto et al. (2019) - Nicole L. Kinlock; Lisa Prowant; Emily M. Herstoff; Catherine M. Foley; Morodoluwa Akin‐Fajiye; Nicole Bender; Mihir Umarani; Hae Yeong Ryu; Bilgecan Şen; Jessica Gurevitch (Global Ecology and Biogeography, 2019)
Menegotto and colleagues’ (2019) commentary on our paper (Kinlock et al., 2018) does not negate our findings, but by recategorizing and reanalysing a portion of our data set, advances our knowledge of the latitudinal diversity gradients (LDGs) in marine ecosystems, particularly emphasizing different findings for benthic LDGs as a result of the recategorization of the data. Furthermore, we see the contribution by Menegotto et al. (2019) as highlighting the importance of scientific transparency; we believe that this insight into the nature of LDGs in marine systems would have been delayed, if not unobtainable, had we not provided fully transparent methods and complete data in our paper.

Long-term trends in large-scale circulation behaviour and wind storms for North Atlantic islands: a multi-data analysis using ERA-20C and meteorological station data - Aideen M. Foley (Climatic Change, 2019)

Microbial assemblages reflect environmental heterogeneity in alpine streams - Scott Hotaling; Mary E. Foley; Lydia H. Zeglin; Debra S. Finn; Lusha M. Tronstad; J. Joseph Giersch; Clint C. Muhlfeld; David W. Weisrock (Global Change Biology, 2019)
Alpine streams are dynamic habitats harboring substantial biodiversity across small spatial extents. The diversity of alpine stream biota is largely reflective of environmental heterogeneity stemming from varying hydrological sources. Globally, alpine stream diversity is under threat as meltwater sources recede and stream conditions become increasingly homogeneous. Much attention has been devoted to macroinvertebrate diversity in alpine headwaters, yet to fully understand the breadth of climate change threats, a more thorough accounting of microbial diversity is needed. We characterized microbial diversity (specifically Bacteria and Archaea) of 13 streams in two disjunct Rocky Mountain subranges through 16S rRNA gene sequencing. Our study encompassed the spectrum of alpine stream sources (glaciers, snowfields, subterranean ice, and groundwater) and three microhabitats (ice, biofilms, and streamwater). We observed no difference in regional (γ) diversity between subranges but substantial differences in diversity among (β) stream types and microhabitats. Within‐stream (α) diversity was highest in groundwater‐fed springs, lowest in glacier‐fed streams, and positively correlated with water temperature for both streamwater and biofilm assemblages. We identified an underappreciated alpine stream type—the icy seep—that are fed by subterranean ice, exhibit cold temperatures (summer mean

A response to “Media representation of hemlock woolly adelgid management risks: a case study of science communication and invasive species control,” published in biological invasions online on September 18, 2018 - Scott M. Salom; Gina Davis; Joseph Elkinton; Jeremiah Foley; Nathan Havill; Carrie Jubb; Albert Mayfield; Tom McAvoy; Rusty Rhea; R. Talbot Trotter; Mark Whitmore (Biological Invasions, 2019)

A baseline analysis of coastal water quality of the port Honduras marine reserve, Belize: a critical habitat for sport fisheries - Brenna M. Sweetman; James R. Foley; Michael K. Steinberg (Environmental Biology of Fishes, 2019)

Heard but not seen: Occurrence of Kogia spp. along the western North Atlantic shelf break - Lynne E. W. Hodge; Simone Baumann‐Pickering; John A. Hildebrand; Joel T. Bell; Erin W. Cummings; Heather J. Foley; Ryan J. McAlarney; William A. McLellan; D. Ann Pabst; Zachary T. Swaim; Danielle M. Waples; Andrew J. Read (Marine Mammal Science, 2018)

King Penguin populations increase on South Georgia but explanations remain elusive - C. M. Foley; T. Hart; H. J. Lynch (Polar Biology, 2018)

Effects of DHA on Hippocampal Autophagy and Lysosome Function After Traumatic Brain Injury - Yan Yin; Eric Li; George Sun; Hong Q. Yan; Lesley M. Foley; Liwia A. Andrzejczuk; Insiya Y. Attarwala; T. Kevin Hitchens; Kirill Kiselyov; C. Edward Dixon; Dandan Sun (Molecular Neurobiology, 2018)

Long-term laboratory culture causes contrasting shifts in tolerance to two marine pollutants in copepods of the genus Tigriopus - Patrick Y. Sun; Helen B. Foley; Leslie Wu; Charlene Nguyen; Shiven Chaudhry; Vivien W. W. Bao; Kenneth M. Y. Leung; Suzanne Edmands (Environmental Science and Pollution Research, 2018)

Explaining global variation in the latitudinal diversity gradient: Meta‐analysis confirms known patterns and uncovers new ones - Nicole L. Kinlock; Lisa Prowant; Emily M. Herstoff; Catherine M. Foley; Morodoluwa Akin‐Fajiye; Nicole Bender; Mihir Umarani; Hae Yeong Ryu; Bilgecan Şen; Jessica Gurevitch (Global Ecology and Biogeography, 2018)
Aim The pattern of increasing biological diversity from high latitudes to the equator [latitudinal diversity gradient (LDG)] has been recognized for > 200 years. Empirical studies have documented this pattern across many different organisms and locations. Our goal was to quantify the evidence for the global LDG and the associated spatial, taxonomic and environmental factors. We performed a meta‐analysis on a large number of individual LDGs that have been published in the 14 years since Hillebrand's ground‐breaking meta‐analysis of the LDG, using meta‐analysis and meta‐regression approaches largely new to the fields of ecology and biogeography. Location Global. Time period January 2003–September 2015. Major taxa studied Bacteria, protists, plants, fungi and animals. Methods We synthesized the outcomes of 389 individual cases of LDGs from 199 papers published since 2003, using hierarchical mixed‐effects meta‐analysis and multiple meta‐regression. Additionally, we re‐analysed Hillebrand's original dataset using modern methods. Results We confirmed the generality of the LDG, but found the pattern to be weaker than was found in Hillebrand's study. We identified previously unreported variation in LDG strength and slope across longitude, with evidence that the LDG is strongest in the Western Hemisphere. Locational characteristics, such as habitat and latitude range, contributed significantly to LDG strength, whereas organismal characteristics, including taxonomic group and trophic level, did not. Modern meta‐analytical models that incorporate hierarchical structure led to more conservative and sometimes contrasting effect size estimates relative to Hillebrand's initial analysis, whereas meta‐regression revealed underlying patterns in Hillebrand's dataset that were not apparent with a traditional analysis. Main conclusions We present evidence of global latitudinal, longitudinal and habitat‐based patterns in the LDG, which are apparent across both marine and terrestrial realms and over a broad taxonomic range of organisms, from bacteria to plants and vertebrates.

Ecological regime shift drives declining growth rates of sea turtles throughout the West Atlantic - Karen A. Bjorndal; Alan B. Bolten; Milani Chaloupka; Vincent S. Saba; Cláudio Bellini; Maria A. G. Marcovaldi; Armando J. B. Santos; Luis Felipe Wurdig Bortolon; Anne B. Meylan; Peter A. Meylan; Jennifer Gray; Robert Hardy; et al. (Global Change Biology, 2017)
Somatic growth is an integrated, individual‐based response to environmental conditions, especially in ectotherms. Growth dynamics of large, mobile animals are particularly useful as bio‐indicators of environmental change at regional scales. We assembled growth rate data from throughout the West Atlantic for green turtles, Chelonia mydas , which are long‐lived, highly migratory, primarily herbivorous mega‐consumers that may migrate over hundreds to thousands of kilometers. Our dataset, the largest ever compiled for sea turtles, has 9690 growth increments from 30 sites from Bermuda to Uruguay from 1973 to 2015. Using generalized additive mixed models, we evaluated covariates that could affect growth rates; body size, diet, and year have significant effects on growth. Growth increases in early years until 1999, then declines by 26% to 2015. The temporal (year) effect is of particular interest because two carnivorous species of sea turtles—hawksbills, Eretmochelys imbricata, and loggerheads, Caretta caretta —exhibited similar significant declines in growth rates starting in 1997 in the West Atlantic, based on previous studies. These synchronous declines in productivity among three sea turtle species across a trophic spectrum provide strong evidence that an ecological regime shift ( ERS ) in the Atlantic is driving growth dynamics. The ERS resulted from a synergy of the 1997/1998 El Niño Southern Oscillation ( ENSO )—the strongest on record—combined with an unprecedented warming rate over the last two to three decades. Further support is provided by the strong correlations between annualized mean growth rates of green turtles and both sea surface temperatures ( SST ) in the West Atlantic for years of declining growth rates ( r = −.94) and the Multivariate ENSO Index ( MEI ) for all years ( r = .74). Granger‐causality analysis also supports the latter finding. We discuss multiple stressors that could reinforce and prolong the effect of the ERS . This study demonstrates the importance of region‐wide collaborations.

Development and dissection of diagnostic SNP markers for the downy mildew resistance genes Pl Arg and Pl 8 and maker-assisted gene pyramiding in sunflower (Helianthus annuus L.) - L. L. Qi; Z. I. Talukder; B. S. Hulke; M. E. Foley (Molecular Genetics and Genomics, 2017)

White matter hyperintensities correlate to cognition and fiber tract integrity in older adults with HIV - Christa Watson; Edgar Busovaca; Jessica M. Foley; I. Elaine Allen; Christopher G. Schwarz; Neda Jahanshad; Talia M. Nir; Pardis Esmaeili-Firidouni; Benedetta Milanini; Howard Rosen; Owen T. Carmichael; Paul M. Thompson; et al. (Journal of NeuroVirology, 2017)

Long-term resource use and foraging specialization in male loggerhead turtles - Mariela Pajuelo; Karen A. Bjorndal; Michael D. Arendt; Allen M. Foley; Barbara A. Schroeder; Blair E. Witherington; Alan B. Bolten (Marine Biology, 2016)

The Kraken in the Aquarium: Questions that Urgently Need to be Addressed in Order to Advance Marine Conservation - John A. Cigliano; Amy Bauer; Megan M. Draheim; Melissa M. Foley; Carolyn J. Lundquist; Julie-Beth McCarthy; Katheryn W. Patterson; Andrew J. Wright; E. C. M. Parsons (Frontiers in Marine Science, 2016)

Sexual Health Concerns Among Cancer Survivors: Testing a Novel Information-Need Measure Among Breast and Prostate Cancer Patients - Sheila A. Crowley; Sallie M. Foley; Daniela Wittmann; Christina H. Jagielski; Rodney L. Dunn; Patricia M. Clark; Jennifer J. Griggs; Catherine Peterson; Marcia Leonard; Lawrence C. An; John T. Wei; James E. Montie; et al. (Journal of Cancer Education, 2016)

Species discovery and validation in a cryptic radiation of endangered primates: coalescent‐based species delimitation in M adagascar's mouse lemurs - Scott Hotaling; Mary E. Foley; Nicolette M. Lawrence; Jose Bocanegra; Marina B. Blanco; Rodin Rasoloarison; Peter M. Kappeler; Meredith A. Barrett; Anne D. Yoder; David W. Weisrock (Molecular Ecology, 2016)
Implementation of the coalescent model in a Bayesian framework is an emerging strength in genetically based species delimitation studies. By providing an objective measure of species diagnosis, these methods represent a quantitative enhancement to the analysis of multilocus data, and complement more traditional methods based on phenotypic and ecological characteristics. Recognized as two species 20 years ago, mouse lemurs (genus Microcebus ) now comprise more than 20 species, largely diagnosed from mt DNA sequence data. With each new species description, enthusiasm has been tempered with scientific scepticism. Here, we present a statistically justified and unbiased Bayesian approach towards mouse lemur species delimitation. We perform validation tests using multilocus sequence data and two methodologies: (i) reverse‐jump Markov chain Monte Carlo sampling to assess the likelihood of different models defined a priori by a guide tree, and (ii) a Bayes factor delimitation test that compares different species‐tree models without a guide tree. We assess the sensitivity of these methods using randomized individual assignments, which has been used in bpp studies, but not with Bayes factor delimitation tests. Our results validate previously diagnosed taxa, as well as new species hypotheses, resulting in support for three new mouse lemur species. As the challenge of multiple researchers using differing criteria to describe diversity is not unique to Microcebus , the methods used here have significant potential for clarifying diversity in other taxonomic groups. We echo previous studies in advocating that multiple lines of evidence, including use of the coalescent model, should be trusted to delimit new species.

Genetics and mapping of a novel downy mildew resistance gene, Pl 18 , introgressed from wild Helianthus argophyllus into cultivated sunflower (Helianthus annuus L.) - L. L. Qi; M. E. Foley; X. W. Cai; T. J. Gulya (Theoretical and Applied Genetics, 2016)

Soil‐Hydrological Responses to Rainfall Variation in a Subtropical Australian Landscape - S. Kodur; J. B. Robinson; J. L. Foley; D. M. Silburn (Irrigation and Drainage, 2015)
Reliable water supply for farming is a global concern, including the Lockyer Valley region, Australia. Knowledge of rainfall variation and resulting irrigation demand and deep drainage can improve crop water use and minimize salinity. Therefore, we modelled irrigation demand and deep drainage for different land‐use types of the Lockyer Valley and classified them according to rainfall. During the periods of extremely low rainfall (mean = 468 mm yr ‐1 ), deep drainage fell by 35–239 mm yr ‐1 , whereas irrigation demand rose by 160–310 mm yr ‐1 , relative to extremely high rainfall (1138 mm yr ‐1 ). With all land‐use types, deep drainage rose with water input, but it was consistent in the order (mean, mm yr ‐1 ): lucerne (8–11), native grass (13), sorghum–wheat sequence (37–64), bare fallow (169) and sweetcorn–broccoli–bean sequence (225). Decadal trends in irrigation demand and deep drainage signalled a raising future irrigation demand; and in turn potential deep drainage risks if irrigation is not managed wisely. These findings will have broader implications for crop and environment management under rainfall variation. Copyright © 2015 John Wiley & Sons, Ltd.

Using Ecological Thresholds to Inform Resource Management: Current Options and Future Possibilities - Melissa M. Foley; Rebecca G. Martone; Michael D. Fox; Carrie V. Kappel; Lindley A. Mease; Ashley L. Erickson; Benjamin S. Halpern; Kimberly A. Selkoe; Peter Taylor; Courtney Scarborough (Frontiers in Marine Science, 2015)

Variation in tolerance to common marine pollutants among different populations in two species of the marine copepod Tigriopus - Patrick Y. Sun; Helen B. Foley; Vivien W. W. Bao; Kenneth M. Y. Leung; Suzanne Edmands (Environmental Science and Pollution Research, 2015)

Rapid water quality change in the E lwha R iver estuary complex during dam removal - Melissa M. Foley; Jeffrey J. Duda; Matthew M. Beirne; Rebecca Paradis; Andrew Ritchie; Jonathan A. Warrick (Limnology and Oceanography, 2015)
Dam removal in the United States is increasing as a result of structural concerns, sedimentation of reservoirs, and declining riverine ecosystem conditions. The removal of the 32 m Elwha and 64 m Glines Canyon dams from the Elwha River in Washington, U.S.A., was the largest dam removal project in North American history. During the 3 yr of dam removal—from September 2011 to August 2014—more than ten million cubic meters of sediment was eroded from the former reservoirs, transported downstream, and deposited throughout the lower river, river delta, and nearshore waters of the Strait of Juan de Fuca. Water quality data collected in the estuary complex at the mouth of the Elwha River document how conditions in the estuary changed as a result of sediment deposition over the 3 yr the dams were removed. Rapid and large‐scale changes in estuary conditions—including salinity, depth, and turbidity—occurred 1 yr into the dam removal process. Tidal propagation into the estuary ceased following a large sediment deposition event that began in October 2013, resulting in decreased salinity, and increased depth and turbidity in the estuary complex. These changes have persisted in the system through dam removal, significantly altering the structure and functioning of the Elwha River estuary ecosystem.

Seventy‐One Important Questions for the Conservation of Marine Biodiversity - E. C. M. PARSONS; BRETT FAVARO; A. ALONSO AGUIRRE; AMY L. BAUER; LOUISE K. BLIGHT; JOHN A. CIGLIANO; MELINDA A. COLEMAN; ISABELLE M. CÔTÉ; MEGAN DRAHEIM; STEPHEN FLETCHER; MELISSA M. FOLEY; REBECCA JEFFERSON; et al. (Conservation Biology, 2014)
The ocean provides food, economic activity, and cultural value for a large proportion of humanity. Our knowledge of marine ecosystems lags behind that of terrestrial ecosystems, limiting effective protection of marine resources. We describe the outcome of 2 workshops in 2011 and 2012 to establish a list of important questions, which, if answered, would substantially improve our ability to conserve and manage the world's marine resources. Participants included individuals from academia, government, and nongovernment organizations with broad experience across disciplines, marine ecosystems, and countries that vary in levels of development. Contributors from the fields of science, conservation, industry, and government submitted questions to our workshops, which we distilled into a list of priority research questions. Through this process, we identified 71 key questions. We grouped these into 8 subject categories, each pertaining to a broad component of marine conservation: fisheries, climate change, other anthropogenic threats, ecosystems, marine citizenship, policy, societal and cultural considerations, and scientific enterprise. Our questions address many issues that are specific to marine conservation, and will serve as a road map to funders and researchers to develop programs that can greatly benefit marine conservation. Setenta y Un Preguntas Importantes para la Conservación de la Biodiversidad Marina

Four species of arboreal folivore show differential tolerance to a secondary metabolite - Lora M. Jensen; Ian R. Wallis; Karen J. Marsh; Ben D. Moore; Natasha L. Wiggins; William J. Foley (Oecologia, 2014)

Long-term behavior at foraging sites of adult female loggerhead sea turtles (Caretta caretta) from three Florida rookeries - Allen M. Foley; Barbara A. Schroeder; Robert Hardy; Sandra L. MacPherson; Mark Nicholas (Marine Biology, 2014)

Spatial and Seasonal Variation of Dissolved Organic Carbon (DOC) Concentrations in Irish Streams: Importance of Soil and Topography Characteristics - Wen Liu; Xianli Xu; Nicola M. McGoff; James M. Eaton; Paul Leahy; Nelius Foley; Gerard Kiely (Environmental Management, 2014)

Time-scale and state dependence of the carbon-cycle feedback to climate - Matteo Willeit; Andrey Ganopolski; Daniela Dalmonech; Aideen M. Foley; Georg Feulner (Climate Dynamics, 2014)

Climate change response in Europe: what’s the reality? Analysis of adaptation and mitigation plans from 200 urban areas in 11 countries - D. Reckien; J. Flacke; R. J. Dawson; O. Heidrich; M. Olazabal; A. Foley; J. J.-P. Hamann; H. Orru; M. Salvia; S. De Gregorio Hurtado; D. Geneletti; F. Pietrapertosa (Climatic Change, 2014)

Conserving large populations of lions – the argument for fences has holes - S. Creel; M. S. Becker; S. M. Durant; J. M'Soka; W. Matandiko; A. J. Dickman; D. Christianson; E. Dröge; T. Mweetwa; N. Pettorelli; E. Rosenblatt; P. Schuette; et al. (Ecology Letters, 2013)
Packer et al . reported that fenced lion populations attain densities closer to carrying capacity than unfenced populations. However, fenced populations are often maintained above carrying capacity, and most are small. Many more lions are conserved per dollar invested in unfenced ecosystems, which avoid the ecological and economic costs of fencing.

Temporal, spatial, and body size effects on growth rates of loggerhead sea turtles (Caretta caretta) in the Northwest Atlantic - Karen A. Bjorndal; Barbara A. Schroeder; Allen M. Foley; Blair E. Witherington; Michael Bresette; David Clark; Richard M. Herren; Michael D. Arendt; Jeffrey R. Schmid; Anne B. Meylan; Peter A. Meylan; Jane A. Provancha; et al. (Marine Biology, 2013)

A Pharm-Ecological Perspective of Terrestrial and Aquatic Plant-Herbivore Interactions - Jennifer Sorensen Forbey; M. Denise Dearing; Elisabeth M. Gross; Colin M. Orians; Erik E. Sotka; William J. Foley (Journal of Chemical Ecology, 2013)

Sex hormones differentially influence voluntary running activity, food intake and body weight in aging female and male rats - J. Andries Ferreira; Andrea M. Foley; Marybeth Brown (European Journal of Applied Physiology, 2012)

Nest-site selection and nest depredation of semi-aquatic turtles on golf courses - Shawna M. Foley; Steven J. Price; Michael E. Dorcas (Urban Ecosystems, 2012)

Progress in Myrtaceae genetics and genomics: Eucalyptus as the pivotal genus - Dario Grattapaglia; René E. Vaillancourt; Merv Shepherd; Bala R. Thumma; William Foley; Carsten Külheim; Brad M. Potts; Alexander A. Myburg (Tree Genetics & Genomes, 2012)
The status of genomics and genetics research in the Myrtaceae, a large family of dicotyledonous woody plants, is reviewed with Eucalyptus as the focal genus. The family contains over 5,650 species in 130 to 150 genera, predominantly of neo-tropical and Southern Hemisphere distribution. Several genera are well known for their economic importance worldwide. Myrtaceae are typically diploids with small to intermediate genome size. Microsatellites have been developed for several genera while higher throughput marker systems such as diversity arrays technology and single nucleotide polymorphism are available for Eucalyptus . Molecular data have been fundamental to current perspectives on the phylogeny, phylogeography and taxonomy of the Myrtaceae, while numerous studies of genetic diversity have been carried out particularly as it relates to endangered, rare, fragmented, overharvested or economically important species. Large expressed sequence tag collections for species of Eucalyptus have recently become public to support the annotation of the Eucalyptus grandis genome. Transcriptomics in Eucalyptus has advanced by microarrays and next-generation sequencing focusing on wood development. Linkage maps for Eucalyptus display high synteny across species and have been extensively used to map quantitative trait loci for a number of traits including growth, wood quality, disease and insect resistance. Candidate gene-based association genetics have successfully found marker–trait associations for wood and fiber traits. Genomic selection experiments have demonstrated clear potential to improve the efficiency of breeding programs while freeze-tolerant transgenic Eucalyptus trials have recently been initiated. The recently released E. grandis genome, sequenced to an average coverage of 8×, will open up exceptional opportunities to advance Myrtaceae genetics and genomics research.

A novel approach of homozygous haplotype sharing identifies candidate genes in autism spectrum disorder - Jillian P. Casey; Tiago Magalhaes; Judith M. Conroy; Regina Regan; Naisha Shah; Richard Anney; Denis C. Shields; Brett S. Abrahams; Joana Almeida; Elena Bacchelli; Anthony J. Bailey; Gillian Baird; et al. (Human Genetics, 2012)

A rehabilitation exercise program to remediate skeletal muscle atrophy in an estrogen-deficient organism may be ineffective - Marybeth Brown; J. Andries Ferreira; Andrea M. Foley; Kaitlyn M. Hemmann (European Journal of Applied Physiology, 2012)

Palatability mapping: a koala's eye view of spatial variation in habitat quality - Ben D. Moore; Ivan R. Lawler; Ian R. Wallis; Colin M. Beale; William J. Foley (Ecology, 2010)
Ecologists trying to understand the value of habitat to animals must first describe the value of resources contained in the habitat to animals and, second, they must describe spatial variation in resource quality at a resolution relevant to individual animal foraging. We addressed these issues in a study of koalas ( Phascolarctos cinereus ) in a Eucalyptus woodland. We measured beneficial and deterrent chemical characteristics as well as the palatability of trees using a near‐infrared spectroscopic model based on direct feeding experiments. Tree use by koalas was influenced by tree size and foliar quality but was also context‐dependent: trees were more likely to be visited if they were surrounded by small, unpalatable trees or by large, palatable trees. Spatial autocorrelation analysis and several mapping approaches demonstrated that foliar quality is spatially structured in the woodland at a scale relevant to foraging decisions by koalas and that the spatial structure is an important component of habitat quality.

Rapid multi-class multi-residue method for the confirmation of chloramphenicol and eleven nitroimidazoles in milk and honey by liquid chromatography-tandem mass spectrometry (LC-MS) - M. Cronly; P. Behan; B. Foley; E. Malone; S. Martin; M. Doyle; L. Regan (Food Additives & Contaminants: Part A, 2010)

Quantitative Temporal Profiles of Penumbra and Infarction During Permanent Middle Cerebral Artery Occlusion in Rats - Lesley M. Foley; T. Kevin. Hitchens; Brent Barbe; Feng Zhang; Chien Ho; Gutti R. Rao; Edwin M. Nemoto (Translational Stroke Research, 2010)

A Metabolomic Approach to Identifying Chemical Mediators of Mammal–Plant Interactions - David J. Tucker; Ian Robert Wallis; Jessica M. Bolton; Karen J. Marsh; Adam A. Rosser; Ian M. Brereton; Dean Nicolle; William J. Foley (Journal of Chemical Ecology, 2010)

Nutritional Ecology of Ateles chamek in lowland Bolivia: How Macronutrient Balancing Influences Food Choices - Annika M. Felton; Adam Felton; Jeff T. Wood; William J. Foley; David Raubenheimer; Ian R. Wallis; David B. Lindenmayer (International Journal of Primatology, 2009)

Functional Consequences of HIV-Associated Neuropsychological Impairment - Ashley A. Gorman; Jessica M. Foley; Mark L. Ettenhofer; Charles H. Hinkin; Wilfred G. van Gorp (Neuropsychology Review, 2009)

Comprehensive N-Methyl Scanning of a Potent Peptide Inhibitor of Malaria Invasion into Erythrocytes Leads to Pharmacokinetic Optimization of the Molecule - Denis Scanlon; Karen S. Harris; Andrew M. Coley; John A. Karas; Joanne L. Casey; Andrew B. Hughes; Michael Foley (International Journal of Peptide Research and Therapeutics, 2008)

Methyl jasmonate does not induce changes in Eucalyptus grandis leaves that alter the effect of constitutive defences on larvae of a specialist herbivore - M. L. Henery; I. R. Wallis; C. Stone; W. J. Foley (Oecologia, 2008)

Effects of poaching on bull mating success in a free ranging African elephant (Loxodonta africana) population in Tarangire National Park, Tanzania - D. R. S. Ishengoma; A. M. Shedlock; C. A. H. Foley; L. J. Foley; S. K. Wasser; S. T. Balthazary; B. M. Mutayoba (Conservation Genetics, 2008)

Seasonal patterns in biomass smoke pollution and the mid 20th‐century transition from Aboriginal to European fire management in northern Australia - David M. J. S. Bowman; Joanne K. Dingle; Fay H. Johnston; David Parry; Michael Foley (Global Ecology and Biogeography, 2007)
Aim Globally, most landscape burning occurs in the tropical savanna biome, where fire is a characteristic of the annual dry season. In northern Australia there is uncertainty about how the frequency and timing of dry season fires have changed in the transition from Aboriginal to European fire management. Location In the tropical eucalypt savannas that surround the city of Darwin in the northwest of the Northern Territory of Australia. Methods Our study had three parts: (1) we developed a predictive statistical model of mean mass (µg) of particulates 10 µm or less per cubic metre of air (PM 10 ) using visibility and other meteorological data in Darwin during the dry seasons of 2000 and 2004; (2) we tested the model and its application to the broader air shed by (a) matching the prediction of this model to PM 10 measurements made in Darwin in 2005, (b) matching the predictions to independent measurements at two locations 20 km to the north and south of Darwin and (c) matching peaks in PM 10 to known major fire events in the region (2000–01 dry seasons); and (3) we used the model to explore changes in air quality over the last 50 years, a period that spans the transition from Aboriginal to European land management. Results We demonstrated that visibility data can be used reliably as a proxy for biomass burning across the largely uncleared tropical savannas inland of Darwin. Validations using independent measurements demonstrated that our predictive model was robust, and geographically and temporally representative of the regional airshed. We used the model to hindcast and found that seasonal air quality has changed since 1955, with a trend to increasing PM 10 concentrations in the early dry season. Main conclusions The results suggest that the transition from Aboriginal to European land management has been associated with an increase in fire activity in the early months of the dry season.

Seasonal patterns in biomass smoke pollution and the mid 20th-century transition from Aboriginal to European fire management in northern Australia - David M. J. S. Bowman; Joanne K. Dingle; Fay H. Johnston; David Parry; Michael Foley (Global Ecology and Biogeography, 2006)

MRI evaluation of topical heat and static stretching as therapeutic modalities for the treatment of eccentric exercise-induced muscle damage - R. C. Jayaraman; R. W. Reid; J. M. Foley; B. M. Prior; G. A. Dudley; K. W. Weingand; R. A. Meyer (European Journal of Applied Physiology, 2004)

Comparison of the climate simulated by the CCM3 coupled to two different land-surface models - Delire C.; Levis S.; Bonan G.; Foley J.; Coe M.; Vavrus S. (Climate Dynamics, 2002)

Coping with chemical complexity in mammal-plant interactions: near-infrared spectroscopy as a predictor of Eucalyptus foliar nutrients and of the feeding rates of folivorous marsupials - Allen M. McIlwee; Ivan R. Lawler; Steven J. Cork; William J. Foley (Oecologia, 2001)

Biarticular and monoarticular muscle activation and injury in human quadriceps muscle - Barry M. Prior; Roop C. Jayaraman; Robert W. Reid; Thomas G. Cooper; Jeanne M. Foley; Gary A. Dudley; Ronald A. Meyer (European Journal of Applied Physiology, 2001)

Measurements and Modeling of Carbon and Nitrogen Cycling in Agroecosystems of Southern Wisconsin: Potential for SOC Sequestration during the Next 50 Years - Christopher J. Kucharik; Kristofor R. Brye; John M. Norman; Jonathan A. Foley; Stith T. Gower; Larry G. Bundy (Ecosystems, 2001)

Cation partitioning versus temperature in spinel: optimization of site occupants - J. A. Foley; S. E. Wright; J. M. Hughes (Physics and Chemistry of Minerals, 2001)

Global response of terrestrial ecosystem structure and function to CO 2 and climate change: results from six dynamic global vegetation models - Wolfgang Cramer; Alberte Bondeau; F. Ian Woodward; I. Colin Prentice; Richard A. Betts; Victor Brovkin; Peter M. Cox; Veronica Fisher; Jonathan A. Foley; Andrew D. Friend; Chris Kucharik; Mark R. Lomas; et al. (Global Change Biology, 2001)
Summary The possible responses of ecosystem processes to rising atmospheric CO 2 concentration and climate change are illustrated using six dynamic global vegetation models that explicitly represent the interactions of ecosystem carbon and water exchanges with vegetation dynamics. The models are driven by the IPCC IS92a scenario of rising CO 2 ( Wigley et al . 1991 ), and by climate changes resulting from effective CO 2 concentrations corresponding to IS92a, simulated by the coupled ocean atmosphere model HadCM2‐SUL. Simulations with changing CO 2 alone show a widely distributed terrestrial carbon sink of 1.4–3.8 Pg C y −1 during the 1990s, rising to 3.7–8.6 Pg C y −1 a century later. Simulations including climate change show a reduced sink both today (0.6–3.0 Pg C y −1 ) and a century later (0.3–6.6 Pg C y −1 ) as a result of the impacts of climate change on NEP of tropical and southern hemisphere ecosystems. In all models, the rate of increase of NEP begins to level off around 2030 as a consequence of the ‘diminishing return’ of physiological CO 2 effects at high CO 2 concentrations. Four out of the six models show a further, climate‐induced decline in NEP resulting from increased heterotrophic respiration and declining tropical NPP after 2050. Changes in vegetation structure influence the magnitude and spatial pattern of the carbon sink and, in combination with changing climate, also freshwater availability (runoff). It is shown that these changes, once set in motion, would continue to evolve for at least a century even if atmospheric CO 2 concentration and climate could be instantaneously stabilized. The results should be considered illustrative in the sense that the choice of CO 2 concentration scenario was arbitrary and only one climate model scenario was used. However, the results serve to indicate a range of possible biospheric responses to CO 2 and climate change. They reveal major uncertainties about the response of NEP to climate change resulting, primarily, from differences in the way that modelled global NPP responds to a changing climate. The simulations illustrate, however, that the magnitude of possible biospheric influences on the carbon balance requires that this factor is taken into account for future scenarios of atmospheric CO 2 and climate change.

Relationship Between Chemical Functional Groups on Eucalyptus Secondary Metabolites and their Effectiveness as Marsupial Antifeedants - Ivan R. Lawler; Bart; M. Eschler; Darren M. Schliebs; William J. Foley (Journal of Chemical Ecology, 1999)

Distinct site preferences for heavy and light REE in amphibole and the prediction of Amph/L D REE - P. Bottazzi; M. Tiepolo; R. Vannucci; A. Zanetti; R. Brumm; S. F. Foley; R. Oberti (Contributions to Mineralogy and Petrology, 1999)

A genetic model and molecular markers for wild oat (Avena fatua L.) seed dormancy - S. A. Fennimore; W. E. Nyquist; G. E. Shaner; R. W. Doerge; M. E. Foley (Theoretical and Applied Genetics, 1999)

Ecological Example of Conditioned Flavor Aversion in Plant–Herbivore Interactions: Effect of Terpenes of Eucalyptus Leaves on Feeding by Common Ringtail and Brushtail Possums - Ivan R. Lawler; Jessica Stapley; William J. Foley; Bart M. Eschler (Journal of Chemical Ecology, 1999)

Administration of a 5HT 3 receptor antagonist increases the intake of diets containing Eucalyptus secondary metabolites by marsupials - I. R. Lawler; W. J. Foley; G. J. Pass; B. M. Eschler (Journal of Comparative Physiology B, 1998)

Vertebrate Herbivory on Eucalyptus—Identification of Specific Feeding Deterrents for Common Ringtail Possums (Pseudocheirus peregrinus) by Bioassay-Guided Fractionation of Eucalyptus ovata Foliage - David M. Pass; William J. Foley; Bruce Bowden (Journal of Chemical Ecology, 1998)

Intraspecific variation in Eucalyptus secondary metabolites determines food intake by folivorous marsupials - I. R. Lawler; W. J. Foley; B. M. Eschler; D. M. Pass; K. Handasyde (Oecologia, 1998)

s of papers presented at the Fifty-Second Annual Meeting of The Potato Association of America - J. A. Crozier; P. J. Ito; Puente De La Fermin; S. J. Peloquin; P. Severino; E. C. Doll; D. R. Christenson; A. R. Wolcott; Hawkins Arthur; F. D. Howard; Herman Timm; W. J. Flocker; et al. (American Journal of Potato Research, 1968)